(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Today’s web based technology offers many online services in almost every field to communicate and share resources [2], [3]. The web technology overcomes the disadvantage of GSM in which the numbers of messages are limited. The advantage of web technology is that we can send N number of information over the medium .The idea of this paper is patient monitoring system using embedded, networking and cloud computing [4], [5]. It maintains a database of all the patients admitted in the hospital [6], [7], [10], [11]and monitor the Intravenous Infusion pumps drip level and the biological parameters such as heartbeat, body temperature and updating the status[1], [12], [13]. If critical condition is determined it send alert to the analyst of that hospital. The alert contains the data which are listed above. The system is intended to reduce the manual intervention to the most possible levels. The cloud computing helps to maintain the data base in every second [8]. Keywords: MSP 430, Intravenous infusion drip rate, heartbeat, temperature, cloud computing, web technology